Tüntetések Budapesten (1996-1997) - Magyar, Gábor; Páll, Kinga Ágnes; Szabó, Andrea; Szabó, Máté (Szociológiai Szemle, 2024)
The paper focuses on the double topic of protest and protest policing in a new democracy, Hungary. Hungarian protest groups underwent radical changes, from samizdat culture to a more instrumental identity and a more visible and mediated activity. Police had also to break with the past and look for new, democratic models of protest policing. The repressive, state and political police needed a new definition of police practices and role in a new political system under public scrutiny and with western co-operation. How did both actors, the police and civil society, reconstruct their identity, their organisation and role in this new context? How did these actors evolve since the 1989 democratic transition? What problems and expectations became crucial?We introduce three central concepts of our study. We argue that police can basically choose between the classical model of state police and a more recent model of citizen police. The adoption of one of the two models depends on several factors, such as political tradition, political coalition around notions of civil rights, and the strength of civil society and the public sphere. Organised protest itself needs a dense network of associations of civil society and its form or repertoire depends on the level of police repression, rules of access to the media and the existing political institutions. The public sphere, which is our third central topic, will be analysed to show how both protest and protest policing are framed in the public discourse and who, as social or political group, has access to this public sphere. We argue that the type of public sphere is an important factor in explaining both police and protest.The study shows that the more attention is paid by the media to public order operations, the less emphasis is on the coercive means of the police. This evolution can explain to some extent the emphasis put by the police institution on improving their public relations. In a rather crude manner we can say that there is an evolution within the police institution from a state police model towards a citizen police model. The public reactions expressed in the press and political coalitions are major variables explaining the practices of police during protest events. Public reactions do not necessarily coincide with a civil rights oriented police but "moral panics" are always possible and, especially during crisis, the law and order coalition can emerge as the winner of the frame of struggle for public order. However, we can expect that the degree to which the police are responding to public opinion depends on the strength of civil society and the independence of the press. In recent democracies, as in Hungary, civil society has not fully developed and remains weak. We can expect the police to be more dependent on political coalition than in democracies with a fully developed civil society. Protest movements do not always attempt to directly influence political decision-making, but they can use the media in order to put topics on the political agenda. The more open the media are to groups in civil society, the more likely that these groups will use peaceful types of action. However, to access the public sphere often needs to enhance the news value of protest action and, in this sense, requires some degree of rule-breaking. In conclusion, protest and protest policing involve at least three important variables. The first one is the state, state actors, which can be more or less open and more or less repressive. The second one is civil society. When civil society is weak, protest is unlikely as well as control over police by society. The third is the public sphere. If the public sphere is power-oriented (Habermas) and excludes groups from civil society, we are likely to observe more radical actions. The more democratic the public sphere, the more chances are that protest will adopt only a limited rule-breaking behaviour.